Endothelial Cell Density and Central Corneal Thickness following Penetrating Keratoplasty of Acanthamoeba Keratitis Patients – A Retrospective Cross-Sectional Observational Study - Shi, Lei; Fries, Fabian Norbert; Xanthopoulou, Kassandra; Stachon, Tanja; Daas, Loay; Zemova, Elena; Langenbucher, Achim; Seitz, Berthold; Szentmáry, Nóra (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To analyze endothelial cell density (ECD) and central corneal thickness (CCT) following penetrating keratoplasty (PKP) in Acanthamoeba keratitis (AK) patients.Patients and Methods In this retrospective, clinical, single-center, cross-sectional, observational study, patients were enrolled who underwent PKP at the Department of Ophthalmology of Saarland University Medical Center, Homburg/Saar, Germany between May 2008 and December 2016 with the diagnosis of AK. In all, 33 eyes of 33 patients (14 males, 42%) were enrolled; their mean age at the time of surgery was 39.5 ± 14.3 years. Postoperatively, AK patients received topical polyhexamethylene biguanide, propamidine isethionate, neomycin sulphate/gramicidin/polymixin B sulfate, and prednisolone acetate eye drops (5 ×/day each), and the topical treatment was tapered sequentially with 1 drop every 6 weeks over 6 months. CCT was recorded using Pentacam HR Scheimpflug tomography and ECD with the EM-3000 specular microscope before surgery and 3 and 6 months after surgery as well as after the first and second (complete) suture removal.Results ECD tended to decrease significantly from the time point before surgery (2232 ± 296 cells/mm2) to the time point 3 months after surgery (1914 ± 164 cells/mm2; p = 0.080) and to the time point after the first suture removal (1886 ± 557 cells/mm2; p = 0.066) and decrease significantly to the time point after the second suture removal (1650 ± 446 cells/mm2; p = 0.028). CCT did not change significantly over the analyzed time period (p ≥ 0.475).Conclusion In AK, endothelial cell loss does not seem to be accelerated following PKP, despite the postoperative use of diamidine and biguanide. A subsequent prospective comparative study should confirm our retrospective longitudinal analysis.
Keywords: endothelial cell density; corneal thickness; penetrating keratoplasty; Acanthamoeba keratitis; bacterial keratitis; keratoconus